Ratio fluorescence detection of tetracycline by a Eu3+/NH2-MIL-53(Al) composite. Issue 4 (12th January 2021) - Chen, Jing; Xu, Yali; Li, Shuying; Xu, Fanghong; Zhang, Qian
Abstract : Tetracycline detection has been a great concern because of its overuse and difficulty in degrading. Abstract : Tetracycline detection has been a great concern because of its overuse and difficulty in degrading. Here, a detection method with ratio fluorescence was developed by synthesizing Eu 3+ doped nanocomposites with NH2 -MIL-53(Al) nanosheets. After adding tetracycline, the fluorescence intensity at 616 nm characteristic emission peak of Eu 3+ was sensitized by the antenna effect generated from coordinating Eu 3+ with tetracycline, but the fluorescence of NH2 -MIL-53(Al) at 433 nm was quenched by the fluorescence resonance energy transfer between the Eu 3+ -tetracycline composition and NH2 -MIL-53(Al). Therefore, the efficient detection of tetracycline was achieved based on this change of ratio fluorescence signal. The experimental results show that Eu 3+ /NH2 -MIL-53(Al) has excellent selectivity, a wider linear range and a lower detection limit for detecting tetracycline. This method can afford favorable ideas for developing advanced chemical and biological sensors.